Genetic Analysis of Methyl Anthranilate, Mesifurane, Linalool, and Other Flavor Compounds in Cultivated Strawberry (Fragaria × ananassa) - Barbey, Christopher R.; Hogshead, Maxwell H.; Harrison, Benjamin; Schwartz, Anne E.; Verma, Sujeet; Oh, Youngjae; Lee, Seonghee; Folta, Kevin M.; Whitaker, Vance M. (Frontiers in Plant Science, 2021)
The cultivated strawberry (Fragaria ×ananassa) is an economically important fruit crop that is intensively bred for improved sensory qualities. The diversity of fruit flavors and aromas in strawberry result mainly from the interactions of sugars, acids, and volatile organic compounds (VOCs) that are derived from diverse biochemical pathways influenced by the expression of many genes. This study integrates multi-omics analyses to identify QTL and candidate genes for multiple aroma compounds in a complex strawberry breeding population. Novel fruit volatile QTL were discovered for methyl anthranilate, methyl 2-hexenoate, methyl 2-methylbutyrate, mesifurane, and a shared QTL on Chr 3 was found for nine monoterpene and sesquiterpene compounds, including linalool, 3-carene, β-phellandrene, α-limonene, linalool oxide, nerolidol, α-caryophellene, α-farnesene, and β-farnesene. Fruit transcriptomes from a subset of sixty-four individuals were used to support candidate gene identification. For methyl esters including the grape-like methyl anthranilate, a novel ANTHANILIC ACID METHYL TRANSFERASE–like gene was identified. Two mesifurane QTL correspond with the known biosynthesis gene O-METHYL TRANSFERASE 1 and a novel FURANEOL GLUCOSYLTRANSFERASE. The shared terpene QTL contains multiple fruit-expressed terpenoid pathway-related genes including NEROLIDOL SYNTHASE 1 (FanNES1). The abundance of linalool and other monoterpenes is partially governed by a co-segregating expression-QTL (eQTL) for FanNES1 transcript variation, and there is additional evidence for quantitative effects from other terpenoid-pathway genes in this narrow genomic region. These QTL present new opportunities in breeding for improved flavor in commercial strawberry.